Assessment of the purity of isolated cell populations for lineage‐specific chimerism monitoring post haematopoietic stem cell transplantation. Issue 4 (17th September 2013) - Hanson, V.; Adams, B.; Lord, J.; Barker, A.; Poulton, K.; Lee, H.
Abstract Following haematopoietic stem cell transplantation, monitoring the proportion of donor and recipient haematopoiesis in the patient (chimerism) is an influential tool in directing further treatment choices. Short tandem repeat (STR) analysis is a method of chimerism monitoring using DNA isolated from peripheral blood, bone marrow or specific isolated cell lineages such as CD3+ T cells. For lineage‐specific STR analysis on cell populations isolated from peripheral blood, a qualitative estimation of the purity of each isolated population is essential for the correct interpretation of the test data. We describe a rapid, inexpensive method for the determination of purity using a simple flow cytometry method. The method described for assessing the purity of sorted CD3+ cells can be applied to any cell population isolated using the same technology. Data obtained were comparable to results from a commercial polymerase chain reaction (PCR)‐based method for the assessment of purity (Non‐T Genomic Detection Kit, Accumol, Calgary, AB, Canada) (P = 0.59). Of the 303 samples tested by flow cytometry, 290 (95.7%) exceeded 90% purity, and 215 (70.95%) were over 99% pure. There were some outlying samples, showing diversity between samples and the unpredictability of purity of isolated cell populations. This flow cytometry method can be easily assimilated into routine testing protocols, allowing purity assessment in multiple‐sorted cell populations for lineage‐specific chimerism monitoring using a single secondary antibody and giving results comparable to a PCR‐based method. As purity of isolated cell lineages is affected by time after venepuncture and storage temperature, assessment of each sample is recommended to give a reliable indication of sample quality and confidence in the interpretation of the results.